Pengaruh Efektivitas Pemerintah dan Transparansi Anggaran Terhadap Pencapaian SDG 8 - Moh. Rafli; Masdar, Rahma; Furqan, Andi Chairil; Pakawaru, Muhammad Ilham (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This study examines whether government effectiveness and budget transparency affect the achievement of Sustainable Development Goal 8 (SDG 8), which focuses on promoting decent work and sustainable economic growth across countries. Drawing on public financial governance and good governance perspectives, this study employs a quantitative approach using panel data from 115 United Nations member states, comprising 442 observations over the period 2017–2023. Government effectiveness is measured using the Worldwide Governance Indicators, while budget transparency is captured through the Open Budget Survey, with the natural logarithm of GDP included as a control variable. Panel regression techniques are applied to ensure consistency with the cross-country and time-series structure of the data. The results indicate that government effectiveness and budget transparency have positive and statistically significant effects on the achievement of SDG 8. These findings highlight the importance of transparent budgeting practices and effective public sector governance in improving resource allocation efficiency and supporting labor market and economic growth outcomes. This study contributes to the accounting and public sector literature by providing cross-country empirical evidence on the role of public financial governance in advancing sustainable development outcomes related to decent work and economic growth.